Underwater undulatory swimming: study of frequency, amplitude and phase characteristics of the `body wave` - Gavilan, A.; Arellano, R.; Sanders, R. (2006)
The purpose of this study was to analyze wave motions of underwater undulatory swimming (UUS) and to compare these whip-like actions with previous studies developed in butterfly and breaststroke. UUS is characterized by vertical displacements of the body parts such that a wave progresses along the body with most of its power contained in a single sinusoidal harmonic (H1). Progresion of the H1 wave from hip to ankle raises the possibility that energy is transmitted along the whole body in butterfly swimming and from the hips in USS. In UUS upper body segment movements were not part of the body wave and would be used to stabilize position. Increasing values of vertical velocities caudally from hip to knees to ankles appears to be related to maximising horizontal velocity of the CM in UUS. A future analysis of the wake structure generated by UUS and its relationship to wave characteristics seems a logical step for further understanding propulsive mechanisms in UUS.